Polyropylene - natural zeolite composite films - Özmıhçı, Filiz; Balköse, Devrim; Özmıhçı, Filiz (01. Izmir Institute of Technology, 1999)
In this project, preparation and characterization of polypropylene natural zeolite composites were studied. Three different series of preparation methods were performed, hot press, microscope slide, and extrusion. The composites are ranged between 0-10 wt%, 0-50 wt%, and 0-6 wt% zeolites, for hot press, microscope slide, and extrusion respectively.Polymer matrix composites are materials which contain polymers as matrix materials surrounding very small reinforcing fibers or fillers. Polymeric composites have great potential from a manufacturing standpoint and show advantages. Such as they are inexpensive, derive from natural sources, present lower density than mineral fillers, and increases the mechanical properties of the final product.In this research polypropylene was used as a matrix material and natural zeolite as a filler. Natural zeolite particles were modified with polyethylene glycol to break agglomerates and make a homogenous dispersion of natural zeolite in polypropylene matrix. These composites were characterized by using differential scanning calorimetry, thermal gravimetric analyzer, infrared spectrophotometer, optical microscopy, mechanical testing and by density measurement device. It has been found that, branched shaped air pockets existed in hot pressed and extruded composites. This causes low mechanical strength, and the densities of these films also indicate the presence of voids in the composite.
Thesis (Master)--İzmir Institute of Technology, Materials Science and Engineering, Izmir, 1999
Includes bibliographical references (leaves: 104-108)
Text in English; Abstract: Turkish and English
xv, 108 leaves
Keywords: TA418.9.C6 .O96 1999; Composite materials; Polymeric composites; Zeolites; Polypropylene